Acoustic characteristics of English lexical stress produced by native Mandarin speakers - Zhang, Yanhong (Acoustical Society of America, 2008)
Native speakers of Mandarin Chinese have difficulty producing native-like English stress contrasts. Acoustically, English lexical stress is multidimensional, involving manipulation of fundamental frequency (F0), duration, intensity and vowel quality. Errors in any or all of these correlates could interfere with perception of the stress contrast, but it is unknown which correlates are most problematic for Mandarin speakers. This study compares the use of these correlates in the production of lexical stress contrasts by 10 Mandarin and 10 native English speakers. Results showed that Mandarin speakers produced significantly less native-like stress patterns, although they did use all four acoustic correlates to distinguish stressed from unstressed syllables. Mandarin and English speakers’ use of amplitude and duration were comparable for both stressed and unstressed syllables, but Mandarin speakers produced stressed syllables with a higher F0 than English speakers. There were also significant differences in formant patterns across groups, such that Mandarin speakers produced English-like vowel reduction in certain unstressed syllables, but not in others. Results suggest that Mandarin speakers’ production of lexical stress contrasts in English is influenced partly by native-language experience with Mandarin lexical tones, and partly by similarities and differences between Mandarin and English vowel inventories.